Mutant p53 drives an immune cold tumor immune microenvironment in oral squamous cell carcinoma - Yewen Shi; Tongxin Xie; Bingbing Wang; Rong Wang; Yu Cai; Bo Yuan; Frederico O. Gleber-Netto; Xiangjun Tian; Alanis E. Rodriguez-Rosario; Abdullah A. Osman; Jing Wang; Curtis R. Pickering; et al. (Communications Biology, 2022)
Oral squamous cell carcinoma models are presented with defined Trp53 mutations associated with immune checkpoint inhibitor responsiveness, e.g. T122N amino acid change of Tp53 promotes a cold TME enriched with immunosuppressive M2 macrophages resistant to ICI therapy.